The Effects of Production Offshoring on R&D and Innovation in the Home Country - Bernhard Dachs; Bernd Ebersberger (FIW - Research Centre International Economics, 2013)
A strong innovation performance based on R&D, product development and the implementation of advanced production technologies is key for the long-term competitiveness of European economies. This study investigates the effects of production offshoring on R&D and innovation activities of the firm in the home country. The analysis is based on a dataset of more than 3000 manufacturing firms from seven European countries. We employ propensity score matching to compare R&D and innovation activities of firms which have offshored production activities in a previous period to a control group of non-offshoring firms. The analysis finds no negative effect of production offshoring on innovation and technological capabilities of firms in the home country. On contrary, offshoring firms spend significantly more on R&D or product design, and invest more in process innovation than non-offshoring firms. These results support a view on internationalisation of firms that regards offshoring as a strategy of international expansion, and not a passive reaction of firms to a loss of their competitiveness. Our results indicate that this expansion goes hand in hand with innovation and process modernization at home.
Keywords: F23; F61; O31; O33; 330; offshoring; innovation; R&D; home country effects; investment